Possibilidades Analíticas sobre o Desenvolvimento Rural a partir da Nova Economia Institucional: Um Estudo de Caso na Vitivinicultura do Rio Grande do Sul - Claudio Vinicius Silva Farias (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2019)
This paper intends to present as a theoretical essay on the use of the main concepts of the New Institutional Economy (NIE) to understand the phenomenon of rural development, focusing the analysis on the proposals of its main author Douglass North. After an extensive review, we present an analytical model that contemplates the main transformations that took place, in the organizational, technological, competitive and institutional environments, in the viticultural sector of the state of Rio Grande do Sul. From these analyzes, a concept of rural development from the institutional perspective is proposed. The concept seeks to understand rural development more broadly than just an economic look at production in rural settings. It is considered that the proposal undertaken here may qualify the empirical analysis, reaching dimensions not yet explored in rural development studies, such as its historicity and its social and institutional configurations, which condition the interventions of the actors in the territory, producing their trajectories of development.